Prognostic evaluation of tumor-stroma ratio in patients with early stage cervical adenocarcinoma treated by surgery - Tip Pongsuvareeyakul (2018)
Background: The tumor-stroma ratio (TSR) represents the percentage of neoplastic cell components compared to the combined area of neoplastic cells and the surrounding tumor-induced stroma. A low TSR (predomination of stromal component) has been demonstrated to be an independent adverse prognostic factor in cancers of several organs. In cervical carcinoma patients, TSR has been evaluated in only one previous study with different histological types. The present study aimed to assess the prognostic value of TSR in early stage cervical cancer patients with adenocarcinoma histology only. Materials and Methods: Histological slides of patients with early stage (IB-IIA) cervical adenocarcinoma who underwent surgical treatment between January 2003 and December 2011 were reviewed. Patients who had received preoperative chemotherapy were excluded. TSR was categorized as low ( < 50%) and high (≥50%). Correlations between TSR and clinicopathological variables were evaluated. Prognostic values of TSR and other variables were estimated using Cox's regression. Results: Of 131 patients; 38 (29.0%) had low TSR and 93 (71.0%) had high TSR. The patients with low TSR had significantly higher proportions of deep cervical stromal invasion (outer third of wall, p=0.011; residual stroma less than 3 mm, p=0.008) and parametrial involvement (p=0.026). Compared to the patients with high TSR, those with low TSR tended to have lower 5-year disease-free survival rate (83.8% versus 88.9%) and overall survival rate (85.6% versus 90.3%), although the differences were not statistically significant. Low TSR was significantly associated with decreased overall survival in univariate analysis (HR 2.7; 95% CI 1.0-7.0; p=0.041), but not in multivariate analysis. TSR was not significantly associated with decreased disease-free survival. Conclusions: Low TSR is associated with decreased overall survival in patients with early stage cervical adenocarcinoma treated by surgery. However, it was not found to be an independent prognostic predictor in this study.